Documenting potential ethnoveterinary knowledge from the indigenous communities of Cold Desert of Ladakh: A trans-Himalayan region of India - Batool, Zohra; Singh, Kanwaljeet; Gairola, Sumeet (Ethnobotany Research and Applications, 2022)
Background: The study was conducted in the cold-arid region of Ladakh to evaluate the important ethnoveterinary medical plants used by the indigenous inhabitants and to understand the traditional methods of herbal preparation used locally to treat livestock ailments. Methods: Ethnobotanical survey was carried out in 15 villages of the Ladakh region. A total of 105 informants (83 men and 22 women) between the ages of 40-90 years were interviewed using semi-structured questionnaires in the ethnoveterinary survey. The ethnoveterinary data was analyzed using the use-value (UV) and informant consensus factor (ICF). Results: A total of 25 plant species in 22 genera and 14 families were enlisted, which are used to treat various livestock ailments by Ladakh inhabitants. Fabaceae and Asteraceae were the most represented families with the highest number of species (5 each), followed by Lamiaceae (3 species) and Apiaceae (2 species). Based on taxonomic characteristics, 92% of the plants were herbs, and the whole plants (51%) were the most commonly used plant parts. The important locally used medicinal plants based on the higher use-value were Thymus linearis (UV=0.48), Cicer microphyllum (UV=0.31), Corydalis govaniana (UV=0.24). The highest informant consensus factor was recorded for respiratory, viral, and health-related disorders (ICF=1). Conclusion: Livestock plays a significant role in enhancing the socio-economic status of the local inhabitants of the Ladakh region. Documentation of this traditional knowledge provides a more substantial chance to educate the younger generations and help in perseveration and future innovative research of these indigenous plants. Necessary initiatives should be taken at government and public levels to cultivate and preserve these endangered species. Keywords: Medicinal plants, Traditional knowledge, Livestock diseases, Indigenous communities, Ladakh